KORELASI MINAT BELAJAR SISWA DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR MUJAHIDIN - Muhammad Hidayat; Hery Kresnadi; Dyoty Auliya Vilda Ghasya (Universitas Tanjungpura, 2022)
Abstrak : This study aims to determine whether or not there is a correlation between student interest in learning and student learning outcomes in thematic learning in the fourth grade of the Pontianak Mujahidin Elementary School. The research method used is the expost facto method with a quantitative approach. The population in this study amounted to 174 students and the sample used was 52 students. Data collection techniques in this study are indirect communication techniques and documentary study techniques. The instrument (data collection tool) in this study was in the form of a questionnaire (questionnaire) and learning outcomes document for theme 4. The results showed that 77.67% of students' interest in learning at Mujahidin Elementary School in Pontianak was in the